Strategi Guru Dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an Pada Siswa Sekolah Menengah Atas - Syamsuddin, Sitti Chadijah; Sileuw, Marwan; Rokhmah, Siti (Program Pascasarjana IAIN Langsa, 2023)
Effective strategies carried out by teachers are the main indicators in improving the ability to read and write the Qur'an in students in high school. However, scientific discourse that discusses teacher strategies only focuses on the context of planning, constraints and challenges so that the discussion of teacher strategies in improving the ability to read and write the Qur'an tends to be neglected. In line with that, this study focuses on the question of what strategies teachers use to improve students' ability to read and write the Qur'an in senior high schools. To find answers to these questions, this study uses a descriptive qualitative approach based on the results of observations and interviews with teachers and students. The findings in this study reveal that the strategies that teachers use through the jigsaw approach, familiarization with Qur'anic verses, and memorization training during the learning process are not only successful in increasing students' interest, but also improving their ability and strengthening their focus in the Qur'anic learning process. This study also recommends future studies to consider social, cultural and technological factors that affect students' ability to learn.